Elevated Blood Pressure and Behavioral Risk Factors of Non-Communicable Disease Among School-Going Adolescents in Chengalpattu District, India: A Cross-Sectional Study - Harishma Ramesh; Gowthamkarthic Ravichandhiran; Soumya Agadi; Kesavan S; Anand Kumar; Vigneshsamy Muthuchamy (Medsci Publications, 2024)
Background: Elevated Blood Pressure (BP), often termed the "silent killer," is characterized by a BP of 140/90 mmHg or higher, influenced by modifiable and non-modifiable factors, particularly during adolescence. Hypertension prevalence among Indian adolescents varies from 2% to 20.5%. Despite the critical impact of adolescent health on India's overall health landscape, literature on the non-communicable disease (NCD) burden and risk factors among Indian adolescents remains limited. The aim is to assess the prevalence of elevated BP and associated risk factors among school-going adolescents in Chengalpattu district. Methodology: A cross-sectional study was conducted in Chengalpattu district schools. Utilizing ChatGPT, multi-stage simple random sampling was performed to select 206 adolescents. They were surveyed using adapted questionnaire from the WHO Global School-Based Student Health Survey, covering sociodemographic details, behavioral risks, and anthropometric data and data analysis was conducted using SPSS. Results: Among the 206 participants, 54 (26.2%) had elevated BP. Key predictors of elevated BP were age, gender, family history, physical education, and serious injuries. Cyberbullying was also associated with elevated BP (P=0.020). Conclusions: The increasing trend of NCDs necessitates school and community-based campaigns for risk reduction. Further research on cyberbullying and long-term health interventions is recommended to improve adolescent health and reduce NCDs in Chengalpattu and beyond.